2007
DOI: 10.1353/dem.2007.0019
|View full text |Cite
|
Sign up to set email alerts
|

Immigration and living arrangements: Moving beyond economic need versus acculturation

Abstract: Prior research seeking to explain variation in extended family coresidence focused heavily on the potentially competing roles of cultural preferences and socioeconomic and demographic structural constraints. We focus on challenges associated with international immigration as an additional factor driving variation across groups. Using 2000 census data from Mexico and the United States, we compare the prevalence and age patterns of various types of extended family and non-kin living arrangements among Mexican-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 51 publications
4
121
2
1
Order By: Relevance
“…To better understand the adjustments in intergenerational solidarity following international migration, a different perspective is required, namely the consideration of nonmigrant compatriots from the same original regional-cultural contexts (Foner 1997;Nauck 1989;van Hook and Glick 2007). In this paper, we use data from the 2000 Families Study, which covers families from five regions in Turkey who either live in Western Europe today or never left their country (Guveli et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the adjustments in intergenerational solidarity following international migration, a different perspective is required, namely the consideration of nonmigrant compatriots from the same original regional-cultural contexts (Foner 1997;Nauck 1989;van Hook and Glick 2007). In this paper, we use data from the 2000 Families Study, which covers families from five regions in Turkey who either live in Western Europe today or never left their country (Guveli et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the strongest factors for predicting where a household is in its career are socio-demographic, and not economic, in nature (Angel and Tienda 1982;Gyourko and Linneman 1993;Gyourko et al 1999;Evans et al 2000;Skaburskis 2004;Van Hook and Glick 2007). That is not to say that economic factors do not matter, but they are often secondary in determining where a household is in its career.…”
Section: Situating Individuals In Their Housing Careersmentioning
confidence: 99%
“…Several US studies have found that young households are more likely to be crowded than older ones Van Hook and Glick 2007). Part of the reason for this is that, in addition to being cash-strapped, younger households are earlier along in their housing careers, so they are more likely to have small children, who do not require as much space as adults or older children.…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Newly married couples and unmarried youth are more likely to migrate and nuclear families and solitaries should be common in the first generation (Kritz et al, 2000). Van Hook & Glick (2007) show that Mexican Americans and Mexican immigrants of long duration in the US form vertically extended households (as they do in Mexico), whereas horizontal extension arises from a specific economic strategy among recently arrived immigrants who lack family members (Glick et al, 1997;Blank, 1998).…”
Section: Structural Explanationsmentioning
confidence: 99%